2009
DOI: 10.1016/j.ab.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic device for multiplexed protein detection in nano-liter volumes

Abstract: We describe a microfluidic immunoassay device that permits sensitive and quantitative multiplexed protein measurements on nanoliter-scale samples. The device exploits the combined power of integrated microfluidics and optically encoded microspheres to create an array of approximately 100 μm 2 sensors functionalized with capture antibodies directed against distinct targets. This strategy overcomes the need for performing biochemical coupling of affinity reagents to the device substrate, permits multiple protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 20 publications
(20 reference statements)
0
81
0
1
Order By: Relevance
“…Due to their miniaturization and automation, there are a number of advantages of using microfluidic systems, such as less sample/reagent consumption, reduced risk of contamination, less cost per analysis, lower power consumption, enhanced sensitivity and specificity, and higher reliability. Microfluidic systems have been developed for various biological analytical applications, such as DNA analysis [4][5][6][7][8], immunoassay [9][10][11][12][13], and cell analysis [14][15][16][17][18]. Moreover, a number of demonstrations showed that cell culture can be performed on the microfluidic systems to achieve higher throughput and more reliable results [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their miniaturization and automation, there are a number of advantages of using microfluidic systems, such as less sample/reagent consumption, reduced risk of contamination, less cost per analysis, lower power consumption, enhanced sensitivity and specificity, and higher reliability. Microfluidic systems have been developed for various biological analytical applications, such as DNA analysis [4][5][6][7][8], immunoassay [9][10][11][12][13], and cell analysis [14][15][16][17][18]. Moreover, a number of demonstrations showed that cell culture can be performed on the microfluidic systems to achieve higher throughput and more reliable results [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The reliable and high-sensitivity multiplexed protein detection is highly dependant on the quality of all the reagents, in particular, the antibodies. Compared with other methods for immunoassays using optically encoded microbeads [23,27], our method has several advantages. First, our encoding strategy is scalable and very easy to implement with readily available highquality microbeads.…”
Section: Multiplexed Protein Immunoassays and Sensitivitymentioning
confidence: 99%
“…If 10 encoded microbeads are used to interrogate a protein species of interest to provide 10-fold oversampling, 250 different protein species can be analysed within this 100 Â 100 mm area, the typical size of one spot used in conventional printed microarrays [16,45]. Therefore, our method will enable the integration of antibody array fabrication into microfluidic devices for sensitive multiplexed protein analysis [23,39,41,46] and potentially for single cell analysis.…”
Section: Multiplexed Protein Immunoassays and Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Both samples and reagents can be added to the structures down to the nanolitre scale and transferred from one chamber to the next as they are going through a series of reactions. These steps can involve separation, mixing, incubation, washing steps and enzyme reactions with substrates necessary for the immunoassay [133]. It may also ease the automation of reactions alleviating the human error involved in the loss of accuracy and lowering the energy requirements of the assay [134].…”
Section: Miniaturisation Of Immunosensorsmentioning
confidence: 99%